2018
DOI: 10.1371/journal.ppat.1007279
|View full text |Cite
|
Sign up to set email alerts
|

The DH31/CGRP enteroendocrine peptide triggers intestinal contractions favoring the elimination of opportunistic bacteria

Abstract: The digestive tract is the first organ affected by the ingestion of foodborne bacteria. While commensal bacteria become resident, opportunistic or virulent bacteria are eliminated from the gut by the local innate immune system. Here we characterize a new mechanism of defense, independent of the immune system, in Drosophila melanogaster. We observed strong contractions of longitudinal visceral muscle fibers for the first 2 hours following bacterial ingestion. We showed that these visceral muscle contractions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 70 publications
5
69
0
Order By: Relevance
“…Processed peptides from those prepropeptides marked with an asterisk have been identified in mass-spectrometric assays of the adult midgut [ 198 ]. Evidence for release of enteroendocrine peptides (processed or not) and downstream function has been reported for BursA [ 199 201 ], Dh31 [ 202 , 203 ], NPF [ 204 ], and Tk [ 205 ]. Tk, either from neurons terminating near or on the IPCs or from the gut, activates its receptor TkR99D in the IPCs, where it is required for proper regulation of DILP2 and DILP3 expression [ 205 , 206 ].…”
Section: Metabolic and Behavioral Adaptation To Changing Environmentsmentioning
confidence: 99%
“…Processed peptides from those prepropeptides marked with an asterisk have been identified in mass-spectrometric assays of the adult midgut [ 198 ]. Evidence for release of enteroendocrine peptides (processed or not) and downstream function has been reported for BursA [ 199 201 ], Dh31 [ 202 , 203 ], NPF [ 204 ], and Tk [ 205 ]. Tk, either from neurons terminating near or on the IPCs or from the gut, activates its receptor TkR99D in the IPCs, where it is required for proper regulation of DILP2 and DILP3 expression [ 205 , 206 ].…”
Section: Metabolic and Behavioral Adaptation To Changing Environmentsmentioning
confidence: 99%
“…The role of mucosal TRPA1 signaling may be to detect and respond to inflammation within the colon, but studies in Drosophila have shown that colonization of the intestine by pathogenic bacteria can activate contractions of the Drosophila gut via a TRPA1 mechanism which may serve a protective response to rid the intestine of harmful bacteria (Benguettat et al, 2018). It would be interesting to see whether this novel pathway is replicated in the mammalian gut and so would also implicate TRPA1 as a sensor for the gastrointestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…ISC/EB Dl, ILP6, egr, Hh, spi, wg, Upd1, and Upd2 (Ohlstein and Spradling, 2007;Karpowicz et al, 2010;Osman et al, 2012;Tian et al, 2015Tian et al, , 2016Doupe et al, 2018) EC Hh, Dpp, Gbb, Krn, PGRP-SA, PGRP-SB1, PGRP-SC1a, PGRP-SC1b, PGRP-SC2, PGRP-SD, PGRP-LB, Upd1, Upd2, and Upd3 (Werner et al, 2000;Bischoff et al, 2006;Jiang et al, , 2011Osman et al, 2012;Guo et al, 2014;Jiang, 2014, 2017;Lee et al, 2015;Iatsenko et al, 2016) EE AstA, AstC, AstB/Mip, CCHa1, CCHa2, sli, Orcokinin B, CCAP, Nplp2, Gbp5, and ITP (Veenstra et al, 2008;Biteau and Jasper, 2014;Veenstra and Ida, 2014;Ren et al, 2015;Chen et al, 2016a;Benguettat et al, 2018;Rommelaere et al, 2019;Hung et al,…”
Section: Cell Types Gut Peptidesmentioning
confidence: 99%
“…A recent study using the cytoplasmic calcium reporter CaLexA has indicated that dietary amino acids like casein peptone and lysine directly activate intracellular Ca 2+ cascade, an increase in which is associated with peptide release in multiple endocrine cells (Dus et al, 2015;Benguettat et al, 2018;Oh et al, 2019), in Tk + and DH31 + EEs (Park et al, 2016). Consistently, the protein level and release of Tk peptides in EEs are increased in starved flies and other insects to control gut mobility and EC lipogenesis (Winther and Nassel, 2001;Song et al, 2014), while refeeding flies only yeast that contains plenty of amino acids, but not sucrose or coconut oil, blunts the increase in Tk peptide level (Song et al, 2014).…”
Section: Amino Acidsmentioning
confidence: 99%